Root absorbed pesticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Coconut trees can now be protected from defoliation by an annual treatment using a recently developed root absorption technique. A root about one metre from the trunk is incised, a systemic pesticide is injected, and the opening is then closed. The...